(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze the evolution of the concept of technology in nursing used in Brazilian nursing theses and dissertations. Conceptual analysis was used, guided by Rodgers’ evolutionary model. Data collection from February to March 2019, by consulting the reports deposited in the Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel between 2005 and 2018 and, after the capture, there was a descriptive analysis. The antecedents and consequences referred to integrality in care, technology, information, globalization and clinical practice in nursing. Substitute terms are associated with the concept of interest. Related concepts were those presented by researchers such as Merhy and Nietsche. Concept attributes can be categorized as general. It was concluded that the understanding of the concept of technology has evolved theoretically and in application in nursing practice. The concept permeated the nurse’s role in management, education and assistance directly or indirectly related to care.